Wider Suturectomy Before Posterior Distraction for Craniosynostosis. Issue 1 (January 2019) - Kyutoku, Shigeo; Iwanaga, Masahiro; Okamoto, Toyoko; Harada, Atsuko; Ueda, Koichi
Abstract : Abstract: The aim of the surgery for craniosynostosis is to release increased intracranial pressure and to normalize cranial shape. The procedure has developed so far in Japan, from a simple strip craniectomy before 1960s through a total calvarial remodeling after 1970s and later methods of 1990s, such as distraction and its modifications applying to the posterior cranium. Since a distracter needs certain hardness and thickness of the bone, the surgery has to be stood by until 5 to 6 months of age. Modified Jimenez procedure, as a latest option, were applied for very early years of 10 patients with several types of craniosynostosis, in our team in the past 3 years. The experience was small with short follow-up; the results are all good in those volume change and shape. The procedure proved to be another alternative especially prior to posterior distraction of syndromic patients in terms of positive and expedited control in an earlier surgical management.